Diabetes mellitus is associated with worse baseline and less post-treatment recovery of arterial stiffness in patients with primary aldosteronism. (January 2022) - Tsai, Cheng-Hsuan; Wu, Xue-Ming; Liao, Che-Wei; Chen, Zheng-Wei; Pan, Chien-Ting; Chang, Yi-Yao; Lee, Bo-Ching; Chiu, Yu-Wei; Lai, Tai-Shuan; Wu, Vin-Cent; Hung, Chi-Sheng; Lin, Yen-Hung
Background: Aldosterone excess in primary aldosteronism (PA) has been linked to insulin resistance, and diabetes mellitus has been associated with increased arterial stiffness and worse cardiovascular outcomes. However, the impact of diabetes on baseline and post-treatment arterial stiffness in patients with PA is unknown. Methods: This study prospectively enrolled 1071 PA patients, of whom 177 had diabetes and 894 did not. Clinical, biochemical, and brachial-ankle pulse wave velocity (baPWV) data were analyzed at baseline and 1 year after PA-specific treatment. After propensity score matching of age, sex, body mass index, systolic and diastolic blood pressure, hypertension duration, and number of antihypertensive medications, 144 patients with diabetes and 320 without diabetes were included for further analysis. Results: After propensity score matching, the baseline characteristics were balanced between the diabetes and nondiabetes groups except for fasting glucose, HbA1c, and lipid profiles. The patients with diabetes had significantly worse baseline baPWV compared with those without diabetes. After multivariable linear regression, the presence of diabetes mellitus remained a significant predictor of worse baseline mean baPWV (β: 46.3, 95% confidence interval: 2.9–89.7, p = 0.037). After 1 year of PA-specific treatment, only the nondiabetes group had significant recovery of mean baPWV (1661.8 ± 332.3 to 1565.0 ± 329.2 cm/s, p < 0.001; Δ = −96.8 ± 254.6 cm/s). In contrast, the diabetes group had less improvement (1771.2 ± 353.8 cm/s to 1742.0 ± 377.2 cm/s, p = 0.259; Δ = −29.2 ± 263.2 cm/s) even though the systolic and diastolic blood pressure significantly improved in both groups. Conclusion: The presence of diabetes mellitus in PA patients was associated with worse baseline and less post-treatment recovery of arterial stiffness.